International Security and Feminist Sociotechnical Imaginaries: Inclusive Futures for Peace - Digolin, Kimberly Alves [UNESP]; de Araujo de Assis, Jonathan [UNESP] (My University, 2025)
In Hesitant Feminist’s Guide to the Future, Ivana Milojević states that feminist alternative visions for the future diverge from traditional utopianism by challenging notions of natural roles and functions, seeking ways to address current societal issues such as inequality and structural limitations. Building upon this, we explore the intersection of feminist approaches to international security and the concept of sociotechnical imaginaries. By integrating these frameworks, we argue that “feminist sociotechnical imaginaries” offer innovative ways to critique and reimagine security practices, with a focus on inclusivity and equity for peace. This approach challenges traditional state-centric, militarized perspectives on security and highlights the importance of diverse voices in shaping technological and social futures. With this framework, we challenge the presumed neutrality of technological innovations in security and peacebuilding, advocating for participative processes that reflect diverse social realities and ensure more just futures for all social groups.
Keywords: Feminist Futures; Feminist Studies; Sociotechnical Imaginaries